I shall, we shall, and all others will: paradoxical information security behaviour. (9th July 2018) - Snyman, Dirk P.; Kruger, Hennie; Kearney, Wayne D.
Abstract : Purpose: The purpose of this paper is to investigate the lemming effect as a possible cause for the privacy paradox in information security. Design/methodology/approach: Behavioural threshold analysis is used to test for the presence of the lemming effect in information security behaviour. Paradoxical behaviour may be caused by the influential nature of the lemming effect. The lemming effect is presented as a possible cause of the privacy paradox. Findings: The behavioural threshold analysis indicates that the lemming effect is indeed present in information security behaviour and may lead to paradoxical information security behaviour. Practical implications: The analysis of the lemming effect can be used to assist companies in understanding the way employees influence each other in their behaviour in terms of security. By identifying possible problem areas, this approach can also assist in directing their information security education endeavours towards the most relevant topics. Originality/value: This research describes the first investigation of the lemming effect in information security by means of behavioural threshold analysis in practice.